Program Sanitasi Total Berbasis Masyarakat (STBM) untuk Merubah Perilaku Hidup Sehat di Kelurahan Kasunyatan Kota Serang Provinsi Banten - Titi Stiawati (Program Studi Administrasi Negara Universitas Serang Raya, 2021)
This study aims to determine community participation in the Community-Based Total Sanitation Program (STBM) in changing healthy living behavior in the Kasunyatan Village, Serang City, Banten Province. The qualitative research method is the approach used in this study, namely by collecting data through observation, in-depth interviews, and documentation. The results of the study found that the community-based total sanitation program had the benefit of changing people's behavior from the aspect of clean environmental awareness and disposing of water not indiscriminately. Community involvement is a necessary aspect to be able to control locally in realizing a quality environment. Community involvement in sanitation development, starting from planning, implementation to utilization. The community-based total sanitation program is welcomed by the community, but in terms of the amount of assistance, it still does not meet all community needs.